The nucleotide sequence of the cloned rpoD gene for the RNA polymerase sigma subunit from E coli K12. - Burton, Z (1981)
We have determined the nucleotide sequence of the rpoD gene which codes for the sigma subunit of RNA polymerase from E. coli K12. The gene, which we formerly cloned as a HindIII restriction fragment in the transducing phage, charon 25, was recloned into several plasmids. We have determined a 2600 base pair DNA sequence which includes the entire structural gene for sigma. The resulting amino acid sequence agrees with previous information obtained about sigma including the amino acid composition, partial sequence data for the N-terminus, the highly acidic nature of the polypeptide, and the cleavage pattern at cysteines. The molecular weight of 70,263 daltons calculated for the 613 amino acid polypeptides is significantly lower than had been determined previously by SDS polyacrylamide gel analysis.